2020
DOI: 10.1177/2333794x20928200
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Thoracic Empyema—Outcomes of Intrapleural Thrombolytics: Ten Years of Experience

Abstract: Introduction. Pediatric thoracic empyema is a special entity with increasing frequency. Consensus regarding the best management strategy is still evolving. We describe our single-center 10-year experience adopting intrapleural thrombolytics using tissue plasminogen activator as first-line treatment following failure of simple thoracostomy drainage techniques. Methods. Observational prospective study included all children from 1 day to 18 years admitted for parapneumonic effusion and treated with intrapleural t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In this study, the records of 40 patients with empyema were evaluated, of which 60% (24) were boys, and 40% (16) were girls. The mean duration of hospital stay in patients was 16.5 days, ranging from 3 days to 44 day's (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the records of 40 patients with empyema were evaluated, of which 60% (24) were boys, and 40% (16) were girls. The mean duration of hospital stay in patients was 16.5 days, ranging from 3 days to 44 day's (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Also, a study by Hanson et al showed that patients treated with intrapleural alteplase significantly reduced pleural fluid volume more than normal saline (18). Baram et al in their study showed that intrapleural thrombolytics in complicated pediatric thoracic empyema leads to brilliant outcome and should be encouraged, particularly in countries with inadequate resources (24).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis ( Pacilli and Nataraja, 2018 ) and multiple studies have demonstrated equivalent efficacy between VATS and IPFT with urokinase (uPA) ( Sonnappa et al, 2006 ; Marhuenda et al, 2014 ; Sonnappa, 2015 ; Pacilli and Nataraja, 2018 ) or tPA ( St Peter et al, 2009 ; Livingston et al, 2016b ) in treatment of empyema in pediatric patients. As a result, IPFT is recommended as the first line treatment for empyema in pediatrics ( St Peter et al, 2009 ; Kobr et al, 2010 ; Stefanutti et al, 2010 ; Slaats et al, 2019 ; Baram and Yaldo, 2020 ; Livingston et al, 2020 ). Further studies of treatment with tPA (4 mg) alone or with DNase (Dornase; 5 mg) in empyema in pediatric patients (n = 97; sequential injection, 1 h apart) demonstrated that DNase does not improve the efficacy of tPA ( Livingston et al, 2017 ; Livingston et al, 2020 ).…”
Section: Treatment Of Pediatric Empyema With Minimal Mortality: An Example Of the Trendmentioning
confidence: 99%